Sanitation Management Through Government and Business Entity Cooperation Scheme for Realizing a Sustainable City - Andreas Suwito; Dita Oki Berliyanti (Journal Research of Social Science, Economics, and Management, 2025)
Sanitation Management Through Government and Business Entity Cooperation Scheme for Realizing a Sustainable City is a fundamental aspect of achieving sustainable and adequate urban sanitation development, which is essential for realizing healthy, inclusive, and resilient cities. However, local fiscal limitations, suboptimal institutional capacity, and low involvement of multiple stakeholders pose significant challenges to providing safe sanitation services in Depok City and Bogor City. The Public-Private Partnership (PPP) scheme is viewed as a strategic alternative to bridge financing gaps while improving the efficiency and quality of urban sanitation services. This research aims to analyze the challenges of urban sanitation development in Depok and Bogor, identify key factors influencing private sector involvement through PPP schemes, and formulate sustainable urban sanitation development strategies involving the private sector. The research employs a descriptive qualitative approach, with data collection techniques that include in-depth interviews, observations, and document studies involving key informants from local governments, business actors, sanitation practitioners, and community representatives. The results indicate that the main challenges include weak tariff regulation, limited inter-agency coordination, low public awareness, and inadequate integrated fecal sludge management services. The key factors influencing private sector engagement include legal certainty, the project's economic scale, availability of technical data, and the readiness of local government institutions. This research recommends strengthening regulations and planning, establishing regional public service agencies (BLUD) for sanitation management, enhancing multi-stakeholder collaboration, and developing attractive PPP schemes for private partners as part of efforts to accelerate the achievement of safe and sustainable urban sanitation targets.